Dynamic rock fragmentation: thresholds for long runout rock avalanches (Fracture and Structural Integrity, 2014)
The dynamic fragmentation of rock within rock avalanches is examined using the fragmentation concepts introduced by Grady and co-workers. The analyses use typical material values for weak chalk and limestone in order to determine theoretical strain rate thresholds for dynamic fragmentation and resulting fragment sizes. These are found to compare favourably with data obtained from field observations of long runout rock avalanches and chalk cliff collapses in spite of the simplicity of the approach used. The results provide insight as to the energy requirements to develop long runout behaviour and hence may help to explain the observed similarities between large rock avalanches and much smaller scale chalk cliff collapses as seen in Europe.
Keywords: Rock avalanche